A strategy for optimizing the output energy and durability of metal-ion capacitors fabricated with alloy-based anodes - Chojnacka, Agnieszka; Pan, Xuexue; Bachetzky, Christopher; Brunner, Eike; Beguin, Francois (Energy Storage Materials, 2022)
Herein, we disclose a strategy to optimize the performance of metal-ion capacitors (MICs) incorporating an activated carbon (AC)-positive electrode and a battery-type anode with a large specific capacity. The strategy is illustrated on the example of a sodium-ion capacitor (NIC) in which the anodic material is based on the Sn4P3 alloy combined with a hydrothermal hard carbon from glucose (HCG) used to buffer the volumetric changes during sodium insertion/deinsertion in Sn4P3. To simultaneously enhance the specific energy and life span of the NICs, the capacity ratio, Q-/Q+, between the anode and the positive electrical double-layer (EDL) carbon electrode was rigorously adjusted by varying the low presodiation potential Ep- of Sn4P3 and/or the mass of AC. The presented data clearly show that the capacitance of NICs is controlled by the positive EDL electrode and that any change in Q-/Q+, while playing on the mass of this electrode and Ep-, affects their cycle life and output energy in an antagonistic manner, thus revealing the complexity of the realized research. Consequently, the best compromise between the life span (end-of-life criterion reached after more than 10000 cycles) and specific output energy (55 Wh kg−1 at 1 kW kg−1) was found for the NIC with a Q-/Q+ of 7.5 obtained by limiting the presodiation potential of the HCG/Sn4P3 electrode to 0.22 V vs. Na/Na+. Hence, when designing metal-ion capacitors with an alloy-based anode, not only the capacity ratio between the electrodes, but also the mass of the EDL electrode and the sodium insertion depth in the anodic material should be strictly controlled.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Capacity ratio between electrodes; Life span; Metal-ion capacitor; Sn; Specific output energy